Can the endurance training change the pacing strategy during 10 km running performance? - de Assis Manoel, F.; Hilgemberg Figueiredo, D.; Andrade Machado, F. (International Journal of Performance Analysis in Sport, 2018)
The aim of this study was to verify the effect of endurance training on the pacing strategy and analyse the risk of premature fatigue during the 10-km performance in moderately trained runners. Study participants were 14 runners (18-35 years) who had training prescribed with peak velocity (Vpeak) and its time limit (tlim). Three tests were performed on a treadmill: two maximum incrementals for VO2max and Vpeak and one for tlim. The 10-km running performance was evaluated on a 400-m track. The mean velocity, heart rate (HR) and rate of perceived exertion (RPE) were monitored at each trial of 10-km running performance. Evaluations were collected pre and after 4 weeks of endurance training. The RPE and HR increased linearly throughout the test, and the risk of fatigue decreased after 3 km. The pacing strategy used by the participants was the "U" running pace in pre- and post-training. There was improvement in the 10-km run after training (40.8 ± 2.8 vs. 39.6 ± 2.7 min). The study showed that 4 weeks of endurance training does not change the pacing strategy and the risk of premature fatigue. However, the training was responsible for improving the 10-km running performance.